Answer:
(1,-1)
Explanation:
![\large{ \begin{cases} y = 2x - 3 \\ y = - x \end{cases}}](https://img.qammunity.org/2022/formulas/mathematics/college/rxndog7r8r0657tzf816mbx1yunc1fvtb6.png)
Since both are y-isolated equation. We can combine both.
![\large{2x - 3 = - x}](https://img.qammunity.org/2022/formulas/mathematics/college/knztqgcpjtccsd30l7bkhuq58tglgjbcxd.png)
Since we want to solve for x-term, we need to isolate x-term.
So we move from -x which is the right side to x.
![\large{2x - 3 + x = 0} \\ \large{3x - 3 = 0} \\ \large{3x = 3} \\ \large{x = 1}](https://img.qammunity.org/2022/formulas/mathematics/college/gb1v677bwhxv1gjulxhke62ctv11ft9fi9.png)
But we are not done yet. Solving system of equations, you must solve for y-term as well. (Because we have to answer in ordered pairs which are (x, y))
Substitute x = 1 in any given equations but I will substitute x = 1 in y = -x
![\large{y = - x} \\ \large{y = - 1}](https://img.qammunity.org/2022/formulas/mathematics/college/bsee3h2536jrgtv6rn8hyc84ne5ouv9ejw.png)
Since we have got y-value. Therefore the answer is (1,-1)